A cross sectional study to assess awareness regarding rabies amongst medical students of Rajindra hospital, Patiala, Punjab - Singh, Aman Dev; Rochwani, Ritu; Sagar, Ishan; ., Riya; Jain, Ankur (International Journal Of Community Medicine And Public Health, 2019)
Background: Rabies is a preventable enzootic endemic disease in India, it is a viral disease caused by Lysavirus causing acute inflammation of brain in humans and other warm blooded animals. It is typically transmitted through bites from infected animal. Human rabies deaths are almost entirely preventable through prompt delivery of post-exposure prophylaxis (PEP) to victims of bites by rabid animal. Appropriate knowledge regarding rabies and its prevention among medical students is very important to prevent rabies deaths. The aims and objectives of the study were to assess awareness regarding rabies amongst medical students. Methods: This was a cross sectional study which was conducted in month of April 2018. There were total of 496 students, we could obtain the information from 373 students as the questionnaire was given during a theory class and some of the students were absent. A pretested, structured questionnaire was administered to assess their knowledge about rabies, classification and management of bite wounds, including different vaccination schedules, site and dose. The data was entered using Microsoft excel and statically analysed by Epi Info 7. Results: Almost all (97.32%) students knew that rabies is a fatal disease and 78.02% knew that dog was the primary transmitting animal. Only 41.29% students were aware that head, neck and face to be the danger site of bite. Almost all 98.6% students were aware about washing the wound with soap and water as the primary first aid measure following dog bite whereas 0.27% said suturing as first aid measure. Conclusions: Awareness of medical students regarding cause of rabies and its fatality were good but they had less awareness about the danger sites of animal bite.